Issues of Academic Integrity: An Online Course for Students Addressing Academic Dishonesty - Roberts, Camilla Jones; Hai-Jew, Shalin (My University, 2010)
At Kansas State University, an institutional strategy to promote academic integrity involves an honor code that is backed up by the K-State Honor and Integrity System, a student judiciary system, and the “Development and Integrity” course for students who have been found in contravention of the code. This article addresses the honor system, related university policies, and the recent development of the online version of the Development and Integrity course. This article includes an introduction, a survey of the literature, relevant pedagogical theories, a brief background, an overview of the course design and development, and lessons learned.
Keywords: Academic dishonesty; Online course; Development and integrity; Honor code; Honor and integrity system